MANNED-UNMANNED AIRCRAFTS’ COMBAT FORMATIONS IN ACHIEVING AIR SUPERIORITY - BLYSKUN Оleksandr (Повітряна міць України, 2021)
Air control helps to isolate the combat area and conduct operations at a specific place and time without interference from the enemy air, while providing cover for their own forces. Gaining control of the airspace is not a main objective, and is useful only when used as a tool to achieve a more meaningful goal. Once airspace control has been achieved, air power provides the ability to design (demonstrate and apply) military power where and when required; however, dominance in the air is not a permanent state, and it must be constantly fought for after its establishment. There are two levels of air control: air superiority and air supremacy.